Conditions d’émergence et enjeux des communs scientifiques à partir d’une expérimentation lyonnaise - Claire BROSSAUD (Tic & Société)
The article highlights the intellectual filiations and the issues surrounding scientific commons, characterized by activities of collectively managing and sustaining information resources resulting from the research practices. It is based on an experiment that aimed to build a shared hybrid space of research and innovation in the Lyon metropolitan area. First, it shows how the initial social criticism of the scientific commons followed the phenomenon of enclosures. Then, it stresses that they aren’t limited exclusively to digital open science but are also derived from participatory and citizen sciences. Finally, the article identifies three conditions of possibility: epistemological, economic and political. Upon analysis, scientific commons appear less as “goods” to be protected ex nihilo than as a cultural, historical, and cognitive process.